Everyday probability and statistics health, elections, gambling and war - Woolfson, Michael M. (Distributed by World Scientific Pub., 2012)
Probability and statistics impinge on the life of the average person in a variety of ways--as is suggested by the title of this book. Very often, information is provided that is factually accurate but intended to present a biased view. This book presents the important results of probability and statistics without making heavy mathematical demands on the reader. It should enable an intelligent reader to properly assess statistical information and to understand that the same information can be presented in different ways. In this second edition, the author presents a new chapter exploring science and society including the way that scientists communicate with the public on current topics such as global warming. The book also investigates pensions and pension policy, and how they are influenced by changing actuarial tables